Leisure Engagement: Medical Conditions, Mobility Difficulties, and Activity Limitations—A Later Life Perspective. (5th August 2015) - Nilsson, Ingeborg; Nyqvist, Fredrica; Gustafson, Yngve; Nygård, Mikael
Abstract : Objectives . This study aims to investigate the impact of medical conditions, mobility difficulties, and activity limitations on older people's engagement in leisure activities. Methods . The analyses are based on a cross regional survey carried out in 2010 in the Bothnia region (Northern Sweden and Western Finland). A posted questionnaire, which included questions on different aspects of leisure engagement, medical history, and health, was sent out to older persons in the region. The final sample consisted of 5435 persons aged 65, 70, 75, and 80 years. The data was analyzed by using ordinary least squares (OLS) multivariate regression. Results . The most important predictor of leisure engagement abstention among older people is the prevalence of activity limitations, whereas mobility difficulties and medical conditions play less important roles. The strong negative association between activity limitations and leisure engagement remains significant even after we control for individual, sociodemographic characteristics, and country. Discussion . This study provides a window into leisure engagement in later life and factors influencing the magnitude of engagement in leisure activities.